Involvement of median raphe nucleus 5-HT1A receptors in the regulation of generalized anxiety-related defensive behaviours in rats - Vicente, Maria Adrielle [UNESP]; Zangrossi, Helio; Santos, Lucinéia dos [UNESP]; de Macedoa, Carlos Eduardo [UNESP]; Andrade, Telma Gonçalves Carneiro Spera de [UNESP] (Elsevier B.V., 2008)
Changes in 5-HT1A receptor-mediated neurotransmission at the level of the median raphe nucleus (MRN) are reported to affect the expression of defensive responses that are associated with generalized anxiety disorder (e.g. inhibitory avoidance) but not with panic (e.g. escape). The objective of this study was to further explore the involvement of MRN 5-HT1A receptors in the regulation of generalized anxiety-related behaviours. Results of experiment 1 showed that intra-MRN injection of the 5-HT1A/7 receptor agonist 8-OH-DPAT (0.6 nmol) in male Wistar rats impaired the acquisition of inhibitory avoidance, without interfering with the performance of escape in the elevated T-maze test of anxiety. Pre-treatment with the 5-HT1A receptor antagonist WAY-100635 (0.18 nmol) fully blocked this anxiolytic-like effect. As revealed by experiment 2, intra-MRN injection of 8-OH-DPAT (0.6, 3 or 15 nmol) also caused anxiolytic effect in rats submitted to the light-dark transition test, another animal model that has been associated with generalized anxiety. In the same test, intra-MRN injection of WAY-100635 (0.18, 0.37 or 0.74 nmol) caused the opposite effect. Overall, the current findings support the view that MRN 5-HT neurons, through the regulation of 5-HT1A somatodendritic autoreceptors, are implicated in the regulation of generalized anxiety-associated behaviours. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Median raphe nucleus; Serotonin; Generalized anxiety; 8-OH-DPAT and WAY-100635